URGENSI ETIKA DALAM KEABSAHAN JUAL BELI (STUDI KASUS DI PASAR RAYA SANGKUMPAL BONANG) - Ihsan Helmi Lubis; Mu'adil Faizin (Institut agama islam negeri Padangsidimpuan, 2023)
Buying and selling transactions at Pasar Raya Sangkumpal Bonang are carried out with ethics that are not commendable by the seller to the prospective buyer so that the validity of the sale and purchase needs to be reviewed. The method used to solve the problem in this study is a type of field research with a case study approach to the ethics of the seller of Toko X Pasar Raya Sangkumpal Bonang Padangsidimpuan, the data sources in this study are primary and secondary data sources. Primary data sources consist of interviews with sellers and buyers. Meanwhile, secondary data sources refer to journals and books that are relevant to the researcher's discussion. Based on these problems, researchers will analyze using the theory of Islamic business ethics. based on the results of the study that the practice of transactions carried out by sellers and buyers is null and void because there is an element of coercion carried out by the seller.